Sketching : the basics - Eissen, Koos, ....-; Steur, Roselien, ....- (Amsterdam : BIS publishers, 2021)
This book explains the basic sketching techniques and decisions more in depth and provides much more step-by-step example drawings, which makes it even more suitable for students and professionals who want to become better sketchers. Sketching the Basics can be seen as the prequel to Sketching as it is more targeted at the novice designer. The Basics explains the essential techniques and effects more in detail, taking the reader by the hand and guiding him step by step through all the various aspects of drawing that novice designers come up against.
Keywords: Ontwerpen ; tekenen